ANALISIS KETERAMPILAN CHEST PASS PADA SISWA KELAS X AGRIBISNIS PENGOLAHAN HASIL PERTANIAN SMK NEGERI 1 BAWEN - Sigih Ibad Pramono; Gogot Ardyas Moko (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
This study aims to analyze the chest pass skills of basketball students of class X Agribusiness Agricultural Product Processing at SMK Negeri 1 Bawen because Bawen still has difficulty in passing the ball, especially when passing chest pass to his friends. The study used a quantitative approach with a survey method and an instrument in the form of a chest pass assessment rubric. The research sample was all class X students totaling 35 students. Data The data was analyzed descriptively and presented in the form of a percentage showing that the chest pass ability in the